LITERATURE REVIEW MEASUREMENT MODEL OF INDIVIDUAL BEHAVIOR AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR: INDIVIDUAL CHARACTERISTICS, WORK CULTURE AND WORKLOAD - Permata Sari, Desi; Hapzi Ali (Dinasti Publisher, 2022)
The development of a research role from previous research or relevant research is very important, because it can help and function to strengthen theoretical studies and phenomena of the relationship or influence between variables in a study. This article reviews and attempts to confirm the factors that influence individual behavior and organizational citizenship behavior which include individual character, work culture and workload. The purpose of this article is to build a hypothesis of the influence between variables to be used in further research. Human Resource Management literature study results from library research are: 1) individual characteristics affected on individual behavior; 2) work culture influences individual behavior; 3) workload affects individual behavior; 4) individual behavior affects organizational citizenship behavior; 5) individual characteristics affect organizational citizenship behavior; 6) work culture has an effect on organizational citizenship behavior; 7) workload affects organizational citizenship behavior